Meningkatkan Hasil Belajar Matematika Materi Desimal Menggunakan Model Problem Based Learning (PBL) Pada Kelas IV di SDN Gambut 10 - Norsenawati (CV.ITTC INDONESIA, 2024)
The problem in this research is the low learning outcomes of students in mathematics subjects with decimal material, especially in the material of changing ordinary fractions become decimal. This problem is caused by students lack of understanding of decimal material, resulting in low student activity and learning outcomes, as well as because students are still less actively involved in learning. This research uses a qualitative approach with the type of classroom action research (PTK) which consists of 2 cycles. The subjects of this research consisted of 20 class IV students at SDN Gambut 10 in the 2023/2024 academic year. The results of the research show that teacher activity in cycle I and cycle II has increased and reached the